Direito fundamental ao trabalho seguro: efetividade na proteção da saúde do trabalhador - Aquino, Henrique Lourenço de (2024)
The core of this dissertation is to analyze the fundamental right to safe work from the perspective of effectiveness in protecting workers' health, leading to the reduction of work-related risks and consequently decreasing the occurrence of workplace accidents in Brazil. To this end, an in-depth study of the Brazilian legal framework focused on the work environment and the protection of workers' health is necessary. Thus, we will discuss the types of workplace accidents and the legislation related to this topic, as well as regulations concerning workers' safety, hygiene, and health. In this way, the need to mitigate environmental risks to reduce the number of workplace accidents will be demonstrated. Such measures may result from the imposition by the State for organizations to concretely apply existing legislation aimed at reducing inherent work risks, considering that labor should be a means of granting human dignity and not a way to endanger workers' lives